Study of microstructural degradation of a failed pinion gear at a cement plant. (January 2019) - Rajinikanth, V.; Soni, M.K.; Mahato, B.; Ananda Rao, M.
Abstract: The failed pinion gear assembly of a cement plant was analyzed by visual, residual stress, microstructure and mechanical property examination to determine the root cause of its failure. It is observed that the worn out region contains several surface micro cracks, especially closer to the tip (addendum) as compared to the root (dedendum) of the gear tooth profile. The surface analysis of the worn out regions showed depletion of protective chromium oxide layer at the surface and formation of iron oxide scales due to corrosion attack by lubricants, contaminants resulted in micro pitting and subsequent wear. Residual stress measurements showed tensile residual stresses at the tip (face) of the gear teeth and large compressive stresses at the root (flank) of the gear teeth. The cross-sectional microstructure examination revealed the damages due to rolling contact surface fatigue in the form of subsurface dark etched region bands and coarsened carbides in the surface. Apart from this, the difference in the tempered core microstructure below the case hardened layer between the flank and face regions lead to compressive residual stress in case of soft core and tensile stress in case of harder core respectively. The concentration of tensile residual stresses due to untempered core at the tip aided the micro-pitting and micro-cracking due to the rolling contact surface fatigue was responsible for the initiation of surface cracks and final failure of the gear. Highlights: Failure investigation of cement plant piniongear is presented. Rolling sliding contact fatigue (RSCF) is responsible for the failure of the teeth. Microstructural degradation is extensively studied with respect to martensite decay.